Product inventory control at a local brand forum outlet using ABC analysis - Sintia Putri Pradita; Kuncoro Harto Widodo (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
A local brand forum outlet sells Micro, Small, and Medium Enterprises (MSMEs) products with inventory management still carried out manually based on employee experience. The research objectives are to analyze problems related to the inventory system and provide recommendations for planning and controlling inventory systems at a Local Brand Forum (FBL) outlet. Primary data was collected through observation, in-depth interviews, and Focus Group Discussion (FGD). The method used is ABC analysis to obtain the product classification. The results showed that 16 items (19.05%) are included in class A, with a total sales value of 69.55% of the total value for money. Class B has 25 product items (29.76%) with a total sales value of 20.29% of the total value for money. Products in class C are 43 items (51.19%) with a total sales value of 10.16% of the total value for money. As much as 43.75% of products in class A are nine basic commodities which are the basic needs of the Indonesian people, so they have a high priority in inventory control. These results are expected to provide planning and inventory control systems using the ABC class of products to avoid shortages and overstock inventory.